A Meta-Analysis into Multiscreening and Advertising Effectiveness: Direct Effects, Moderators, and Underlying Mechanisms. Issue 3 (27th May 2019) - Segijn, Claire M.; Eisend, Martin
Abstract : Using another media screen while watching television has become a part of people's daily routines. The topic of multiscreening has thus received increased attention from advertising scholars in recent years. To gain a better theoretical understanding of the circumstances under which multiscreening effects occur and to offer practical guidelines to advertisers, the current study synthesizes the results of past studies on multiscreening and advertising and examines the direct effects of multiscreening on both cognitive and affective advertising outcomes, the possible moderators of those effects, and the underlying mechanisms of multiscreening with regard to advertising outcomes. The results indicate a negative direct effect of multiscreening on cognitive outcomes. The effect is weakened, however, by factors related to research, advertising, and media. In addition, the results show no direct or total effect of multiscreening on affective advertising outcomes, but this again depends on various media-, advertising-, and research-related factors. Finally, the results show that attention, enjoyment, and resistance constitute the underlying mechanisms that explain the effect of multiscreening on memory and persuasion.